KAMPANYE ZERO WASTE SEBAGAI GAYA HIDUP PADA MAHASISWA DAN IBU RUMAH TANGGA DI JATINANGOR (ANALISIS SITUASIONAL DAN RENCANA SOLUSI) - Intan, Tania; Wardiani, Sri Rijati (Universitas Merdeka Madiun, 2019)
The Community Service activities that will be carried out in the 2019/2020 academic year are aimed at developing Jatinangor community awareness, especially students and housewives, to manage waste in the principle of Zero Waste. The methods to be used are counseling, poster distribution, and recycling socialization. Based on situational analysis, it is known that the Jatinangor sub-district is a vast educational area, experiencing very rapid progress as indicated by the high frequency of physical development. However, the economic improvement experienced by this region was not matched by good governance, including the household waste management system. The participation of local governments and educational institutions cannot be said to be adequate. The high level of waste production and negative behaviors regarding the relationship with cultural behavior. To overcome this, a more serious and intensive educational effort is needed to change the mentality of individuals and the community of Jatinangor, in order to minimize the production of personal and household waste by applying the Zero Waste principle through 5 R: â€œRefuse, Reduce, Reuse, Recycle, Rotâ€ in everyday life.